Decreased glutamate transport in acivicin resistant Leishmania tarentolae. - Gaétan Roy; Arijit Bhattacharya; Philippe Leprohon; Marc Ouellette (Public Library of Science (PLoS), 2021)
Studies of drug resistance in the protozoan parasites of the genus Leishmania have been helpful in revealing biochemical pathways as potential drug targets. The chlorinated glutamine analogue acivicin has shown good activity against Leishmania cells and was shown to target several enzymes containing amidotransferase domains. We selected a Leishmania tarentolae clone for acivicin resistance. The genome of this resistant strain was sequenced and the gene coding for the amidotransferase domain-containing GMP synthase was found to be amplified. Episomal expression of this gene in wild-type L. tarentolae revealed a modest role in acivicin resistance. The most prominent defect observed in the resistant mutant was reduced uptake of glutamate, and through competition experiments we determined that glutamate and acivicin, but not glutamine, share the same transporter. Several amino acid transporters (AATs) were either deleted or mutated in the resistant cells. Some contributed to the acivicin resistance phenotype although none corresponded to the main glutamate transporter. Through sequence analysis one AAT on chromosome 22 corresponded to the main glutamate transporter. Episomal expression of the gene coding for this transporter in the resistant mutant restored glutamate transport and acivicin susceptibility. Its genetic knockout led to reduced glutamate transport and acivicin resistance. We propose that acivicin binds covalently to this transporter and as such leads to decreased transport of glutamate and acivicin thus leading to acivicin resistance.